ANALISIS KEMAMPUAN LITERASI SAINS SISWA KELAS V DI SD NEGERI BELANCAN - Ni Nyoman Pitayani; Darmayanti , Ni Wayan Sri; Janawati, Desak Putu Anom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the level of scientific literacy ability of fifth-grade students at SD Negeri Belancan in terms of content knowledge, scientific process skills, and the application of science in daily life contexts. This research employed a quantitative descriptive approach. The subjects of the study were all fifth-grade students of SD Negeri Belancan in the 2025/2026 academic year, totaling 26 students. Data were collected through scientific literacy tests and documentation. The data were analyzed by calculating the mean scores, percentages, and categorizing the results based on predetermined criteria. The results showed that the scientific literacy ability of the fifth-grade students at SD Negeri Belancan was in the high to very high category, with an average score of 82.44%. A total of 18 students were classified in the very high category, while 8 students were in the high category. In the content aspect, students demonstrated a good understanding of basic science concepts. In the process aspect, students showed basic abilities in conducting observations and drawing conclusions; however, they still needed improvement in experimental and scientific inquiry activities. In the context aspect, students were able to relate science concepts to everyday life, although most of them still provided simple explanations that lacked deeper scientific reasoning. Based on the findings, it can be concluded that the scientific literacy ability of the fifth-grade students at SD Negeri Belancan is generally high. Nevertheless, scientific process skills and the ability to provide more in-depth scientific explanations still need to be enhanced through more active, contextual, and inquiry-based learning activities.